The Influence of Celebrity Endorsement on the Customer Decision-Making Process Based on the AISAS Model with the Hedonic Value and Functional Value Approaches - Faisal Sa'ban; Yayan Anggriani; Nurwahidah Nurwahidah; Imam Akbar; Khairunnisah Khairunnisah (JURNAL ECONOMINA, 2026)
This study aims to analyze the decision-making process of customers towards celebrity endorsement-based promotions using the AISAS (Attention, Interest, Search, Action, Distribution) model by including hedonic value and functional value as factors influencing attention. Unlike previous studies that generally focus on the impact of celebrity endorsement on interest or purchase decisions, this study develops the AISAS model by establishing hedonic value and functional value as antecedents of attention. The study uses a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. Data were collected through an online survey of 314 respondents who are members of the outdoor product enthusiast community in Indonesia. The results show that most of the relationships between the stages in the AISAS model are significant in explaining the customer decision-making process up to the separation stage. However, hedonic value and functional value do not show a significant impact on attention. This finding indicates that customers’ attention to celebrity endorsement-based promotions is not solely determined by consumers’ perceived emotional or functional value. This study contributes to the development of the consumer behavior-based digital marketing literature by testing the AISAS model integrated with the consumption value approach. Practically, the research results can be used as input for companies in designing the most effective celebrity endorsement-based promotional strategies according to the characteristics of consumer digital behavior.